Stone Clearance Rate in Patients Treated with Percutaneous Nephrolithotomy versus Open Surgery for the Management of Staghorn Renal Calculi - Muhammad Akhtar, Muhammad Saad Ullah, Muhammad Hamza Khan Lodhi, Nadim Aslam, Zeeshan Zafar, Qazi Hussain Raza, Mm Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the stone clearance rate in patients treated with percutaneous nephrolithotomy (PCNL) versus open surgery for the management of staghorn renal calculi. Materials and Methods: In this comparative study, a total number of 200 patients who presented in urology department of Ibn e Sina Hospital and Research Institute Multan with the diagnosis of staghorn stones were included. The study duration was October-2021 to January-2022. Group I: Patients underwent PCNL and Group II patients underwent open surgery for removal of stones. Stone clearance was two weeks of primary procedure. Results: Mean age was 45.53±10. 37 years in PCNL group versus 44.36±10.80 years in open surgery group (p-value 0.44). There were 64% male patients in PCNL group and 62% male patients in open surgery group (p-value 0.77). There were 19% patients who had bilateral stone in PCNL group and 23% in open surgery group (p-value 0.48). Complete staghorn stones were diagnosed in 70% patients in PCNL and in 73% patients in open surgery group (p-value 0.64).Stone clearance rate was 76% patients in PCNL group and 62% patients in open surgery group (p-value 0.032). Conclusion: In patients who have staghorn stones, percutaneous nephrolithotomy (PCNL) is preferable to open surgery in terms of the rate of stone clearance. Keywords: Open surgery, Staghorn stones, percutaneous nephrolithotomy.